Field Free Line Magnetic Particle Imaging - Erbe, Marlitt; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2014)
Marlitt Erbe provides a detailed introduction into the young research field of Magnetic Particle Imaging (MPI) and field free line (FFL) imaging in particular. She derives a mathematical description of magnetic field generation for FFL imaging in MPI. To substantiate the simulation studies on magnetic FFL generation with a proof-of-concept, the author introduces the FFL field demonstrator, which provides the world s first experimentally generated rotated and translated magnetic FFL field complying with the requirements for FFL reconstruction. Furthermore, she proposes a scanner design of considerably enhanced magnetic field quality and efficiency. The author discusses the influence of magnetic field quality optimization on the image quality achieved using efficient Radon-based reconstruction methods, which arise for a line detection scheme, and based on this optimized design, presents a dynamic FFL scanner assembly. Contents Introduction of a Field Free Line for Magnetic Particle Imaging Magnetic Field Free Line Generation A Field Free Line Field Demonstrator Scanner Efficiency and Magnetic Field Quality Analysis Efficient Reconstruction Algorithms A Dynamic Field Free Line Imaging Device Target Groups Academics and practitioners in the fields of magnetic particle imaging, computed tomography, and medical imaging; radiologists and physicians. The Author Marlitt Erbe earned her doctoral degree at the Institute of Medical Engineering, University of Lübeck, under the supervision of Prof. Thorsten M. Buzug. The Editor The series Aktuelle Forschung Medizintechnik is edited by Thorsten M. Buzug.
Keywords: Engineering; Computer simulation; Medical physics; Radiation; Biomedical engineering; Engineering; Biomedical Engineering; Simulation and Modeling; Medical and Radiation Physics; Electronic books